High-strength corrosion-resistant steel and method for producing the same
Patent Information
- Application Number
- CN202610413703.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-31
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-03-31
AI Technical Summary
[0004]本发明提出一种高强度耐腐蚀钢及其制备方法,解决了相关技术中含氮钢在低温环境下韧性下降和耐蚀性不足的问题
本发明中,调控基体中Ti、Nb与N的配比Ti/N=3~3.5、Nb/N=1~1.2,氮会先与Ti、Nb结合,形成TiN和(Ti,Nb)N化合物能够钉轧晶界,细化晶粒,从而产生更多的晶界阻止裂纹的扩展,使得钢在低温下能够更好地吸收和分散能量,有效避免了因游离N析出导致的脆性断裂,显著提升了钢在低温下的韧性;当Ti/N的比例低于上述范围,游离N含量增加,Nb/N低于上述范围,(Ti,Nb)N难以生成;Ti/N和Nb/N的比例高于上述范围,Ti、Nb含量过高,导致晶粒粗化,不仅无法细化晶粒,且会成为应力集中点,引发脆性断裂,导致低温冲击韧性下降;同时,晶粒细化后对腐蚀介质的扩散具有一定的阻碍作用又能提高钢的耐腐蚀性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of steelmaking technology, specifically to a high-strength corrosion-resistant steel and its preparation method. Background Technology
[0002] Steel is widely used in various fields due to its excellent mechanical properties. As the conditions of some applications become more and more demanding, there are stringent requirements for the strength, toughness and corrosion resistance of steel.
[0003] Currently, adding nitrogen to steel can suppress the precipitation of large carbide particles, thereby improving the steel's corrosion resistance and fatigue resistance. However, it is difficult to precisely control the form of nitrogen during the smelting process, easily leading to the generation of free nitrogen. Residual free nitrogen in steel is prone to precipitation at low temperatures, causing low-temperature aging embrittlement, resulting in decreased toughness and increased susceptibility to fracture, severely impacting the service safety of components. Conversely, if existing denitrification processes are used to completely remove free nitrogen from steel, the steel's strength will decrease significantly, while its toughness and corrosion resistance will also decline simultaneously, failing to meet the comprehensive performance requirements of steel materials in various fields. Summary of the Invention
[0004] This invention proposes a high-strength corrosion-resistant steel and its preparation method, which solves the problems of reduced toughness and insufficient corrosion resistance of nitrogen-containing steel in low-temperature environments in related technologies.
[0005] The technical solution of the present invention is as follows: This invention proposes a high-strength corrosion-resistant steel comprising a matrix and a reinforcing phase. The matrix is composed of the following components by mass percentage: C 0.04%~0.08%, Si 0.21%~0.55%, Mn 1.0%~1.5%, Cr 0.5%~1.0%, N 0.015%~0.025%, P ≤0.02%, S ≤0.008%, Ni 0.1%~0.3%, Cu 0.2%~0.5%, Ti 0.045%~0.0875%, Nb 0.015%~0.03%, with the balance being Fe and other unavoidable impurities, wherein Ti / N = 3~3.5 and Nb / N = 1~1.2.
[0006] As a further technical solution, the reinforcing phase includes alumina and silicon carbide-coated cerium oxide.
[0007] As a further technical solution, the method for preparing the alumina and silicon carbide-coated cerium oxide includes the following steps: Alumina, silicon carbide and cerium oxide are mixed, ethanol is added, and the mixture is ball-milled, dried, calcined and ground to obtain alumina and silicon carbide coated cerium oxide.
[0008] As a further technical solution, the mass ratio of cerium oxide, silicon carbide and aluminum oxide is 90:6~8:4~6.
[0009] In this invention, alumina and silicon carbide-coated cerium oxide serve as reinforcing phases, further enhancing the tensile strength of the steel. Uniformly distributed within the steel matrix, these phases force dislocations to bypass or cut through the material during slip, increasing resistance to dislocation movement and thus significantly improving tensile strength. Simultaneously, the alumina, silicon carbide, and cerium oxide particles in the coating layer form a synergistic strengthening effect, further increasing the resistance to dislocation movement and refining the grain size of the steel matrix, reducing grain boundary slip, and avoiding the shortcomings of a single reinforcing phase, resulting in higher tensile strength in the steel. The mass ratio of cerium oxide, silicon carbide, and alumina can be 90:6:4, 90:7:5, or 90:8:6; preferably, the mass ratio is 90:7:5.
[0010] As a further technical solution, the total mass ratio of cerium oxide, silicon carbide and aluminum oxide to the volume ratio of ethanol is 10g:30~40mL.
[0011] As a further technical solution, the ball mill rotates at a speed of 200~400 rpm for 1.5~2 hours.
[0012] As a further technical solution, the drying temperature is 80~100℃ and the time is 12~15h.
[0013] As a further technical solution, the calcination temperature is 850~950℃.
[0014] This invention also proposes a method for preparing high-strength corrosion-resistant steel, comprising the following steps: Weigh the components according to the weight percentage of the matrix, melt them to obtain molten steel; add the reinforcing phase to the molten steel, mix, and continuously cast to obtain a steel billet; The steel billet is heated, rough rolled, finish rolled, cooled, and coiled to obtain high-strength corrosion-resistant steel.
[0015] As a further technical solution, the casting speed of the continuous casting is 2~2.5m / min.
[0016] As a further technical solution, the heating temperature is 1200-1300℃, and the holding time is 60-80 minutes.
[0017] As a further technical solution, descaling is performed before rough rolling, and the initial rolling temperature of rough rolling is 1100~1200℃, and the final rolling temperature is 1030~1130℃.
[0018] As a further technical solution, descaling is performed before finishing rolling, and the initial rolling temperature of finishing rolling is 930~1030℃, and the final rolling temperature is 830~900℃.
[0019] As a further technical solution, during the cooling process, the temperature of the laminar water is 25~30℃, and the cooling rate is 20~30℃ / s.
[0020] As a further technical solution, the winding temperature is 530~600℃.
[0021] The working principle and beneficial effects of this invention are as follows: In this invention, by controlling the ratio of Ti, Nb, and N in the matrix (Ti / N = 3~3.5, Nb / N = 1~1.2), nitrogen will first combine with Ti and Nb to form TiN and (Ti,Nb)N compounds, which can pin grain boundaries, refine grains, and thus generate more grain boundaries to prevent crack propagation. This allows the steel to better absorb and disperse energy at low temperatures, effectively avoiding brittle fracture caused by free N precipitation, and significantly improving the toughness of the steel at low temperatures. When the Ti / N ratio is below the above range, the free N content increases; when the Nb / N ratio is below the above range, (Ti,Nb)N is difficult to form. When the Ti / N and Nb / N ratios are above the above range, the Ti and Nb content is too high, leading to grain coarsening. This not only fails to refine the grains but also becomes a stress concentration point, triggering brittle fracture and causing a decrease in low-temperature impact toughness. At the same time, grain refinement has a certain hindering effect on the diffusion of corrosive media and can also improve the corrosion resistance of the steel. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] In the following examples and comparative examples, alumina has a particle size of 50 nm; silicon carbide has a particle size of 50 nm; and cerium oxide has a particle size of 3 μm.
[0024] Example 1 A high-strength corrosion-resistant steel comprises a matrix and a reinforcing phase. The matrix consists of the following components in mass percentage: C 0.04%, Si 0.21%, Mn 1.0%, Cr 0.5%, N 0.015%, P 0.02%, S 0.008%, Ni 0.1%, Cu 0.2%, Ti 0.045%, Nb 0.015%, with the balance being Fe and other unavoidable impurities. The reinforcing phase is cerium oxide; A high-strength corrosion-resistant steel, comprising the following steps: Weigh the components according to the weight percentage of the matrix, melt them to obtain molten steel; add the reinforcing phase to the molten steel, the mass ratio of molten steel to reinforcing phase is 100:2.5, mix, and continuously cast at a casting speed of 2m / min to obtain steel billet; The steel billet is heated to 1200℃ and held for 80 minutes. Then it is descaled at 20MPa and enters the rough rolling stage. The initial rolling temperature of the rough rolling is 1100℃ and the final rolling temperature is 1030℃. Descaling is performed again at 20MPa and it enters the finish rolling stage. The initial rolling temperature of the finish rolling is 930℃ and the final rolling temperature is 830℃. Then it is placed in laminar water at 25℃ for cooling at a cooling rate of 20℃ / s. Finally, it is coiled at 530℃ to obtain high-strength corrosion-resistant steel.
[0025] Example 2 A high-strength corrosion-resistant steel comprises a matrix and a reinforcing phase. The matrix consists of the following components in mass percentage: C 0.08%, Si 0.55%, Mn 1.5%, Cr 1.0%, N 0.025%, P 0.015%, S 0.007%, Ni 0.3%, Cu 0.5%, Ti 0.0875%, Nb 0.03%, with the balance being Fe and other unavoidable impurities. The reinforcing phase is cerium oxide; A high-strength corrosion-resistant steel, comprising the following steps: Weigh the components according to the weight percentage of the matrix, melt them to obtain molten steel; add the reinforcing phase to the molten steel, the mass ratio of molten steel to reinforcing phase is 100:2.5, mix, and continuously cast at a casting speed of 2.5 m / min to obtain steel billets; The steel billet is heated to 1300℃ and held for 60 minutes. Then, it is descaled at 20MPa and enters the roughing stage. The initial rolling temperature of the roughing stage is 1200℃, and the final rolling temperature is 1130℃. Descaling is performed again at 20MPa, and it enters the finishing stage. The initial rolling temperature of the finishing stage is 1030℃, and the final rolling temperature is 900℃. Then, it is cooled in laminar water at 30℃ with a cooling rate of 30℃ / s. Finally, it is coiled at 600℃ to obtain high-strength corrosion-resistant steel.
[0026] Example 3 A high-strength corrosion-resistant steel comprises a matrix and a reinforcing phase. The matrix consists of the following components in mass percentage: C 0.06%, Si 0.4%, Mn 1.2%, Cr 0.8%, N 0.02%, P 0.016%, S 0.006%, Ni 0.2%, Cu 0.35%, Ti 0.065%, Nb 0.023%, with the balance being Fe and other unavoidable impurities. The reinforcing phase is cerium oxide; A high-strength corrosion-resistant steel, comprising the following steps: Weigh the components according to the weight percentage of the matrix, melt them to obtain molten steel; add the reinforcing phase to the molten steel, the mass ratio of molten steel to reinforcing phase is 100:2.5, mix, and continuously cast at a casting speed of 2.3 m / min to obtain steel billets; The steel billet is heated to 1250℃ and held for 70 minutes. Then it is descaled at 20MPa and enters the roughing stage. The initial rolling temperature of the roughing stage is 1150℃ and the final rolling temperature is 1080℃. Descaling is performed again at 20MPa and it enters the finishing stage. The initial rolling temperature of the finishing stage is 970℃ and the final rolling temperature is 870℃. Then it is placed in laminar water at 25℃ for cooling at a cooling rate of 25℃ / s. Finally, it is coiled at 560℃ to obtain high-strength corrosion-resistant steel.
[0027] Example 4 The only difference between this embodiment and Embodiment 3 is that the reinforcing phase is alumina and silicon carbide coated with cerium oxide; A method for preparing cerium oxide coated with alumina and silicon carbide includes the following steps: Alumina, silicon carbide and cerium oxide were mixed (the mass ratio of cerium oxide, silicon carbide and alumina was 90:6:4), ethanol was added (the total mass of cerium oxide, silicon carbide and alumina to the volume ratio of ethanol was 10g:30mL), ball milled at 200rpm for 2h, dried at 80℃ for 15h, and finally calcined at 850℃ and ground to obtain alumina and silicon carbide coated cerium oxide.
[0028] Example 5 The only difference between this embodiment and Embodiment 3 is that the reinforcing phase is alumina and silicon carbide coated with cerium oxide; A method for preparing cerium oxide coated with alumina and silicon carbide includes the following steps: Alumina, silicon carbide, and cerium oxide were mixed (the mass ratio of cerium oxide, silicon carbide, and alumina was 90:6:4), and ethanol was added (the total mass of cerium oxide, silicon carbide, and alumina to the volume ratio of ethanol was 10g:40mL). The mixture was ball-milled at 400rpm for 1.5h, then dried at 100℃ for 12h, and finally calcined and ground at 900℃ to obtain alumina and silicon carbide coated cerium oxide.
[0029] Example 6 The only difference between this embodiment and Embodiment 4 is that the mass ratio of cerium oxide, silicon carbide, and aluminum oxide is 90:7:5.
[0030] Example 7 The only difference between this embodiment and Embodiment 4 is that the mass ratio of cerium oxide, silicon carbide, and aluminum oxide is 90:8:6.
[0031] Comparative Example 1 The only difference between this comparative example and Example 3 is that the matrix is composed of the following components by mass percentage: C 0.06%, Si 0.4%, Mn 1.2%, Cr 0.8%, N 0.02%, P 0.016%, S 0.006%, Ni 0.2%, Cu 0.35%, Ti 0.08%, Nb 0.03%, with the balance being Fe and other unavoidable impurities.
[0032] Comparative Example 2 The only difference between this comparative example and Example 3 is that the matrix is composed of the following components by mass percentage: C 0.06%, Si 0.4%, Mn 1.2%, Cr 0.8%, N 0.02%, P 0.016%, S 0.006%, Ni 0.2%, Cu 0.35%, Ti 0.05%, Nb 0.01%, with the balance being Fe and other unavoidable impurities.
[0033] Comparative Example 3 The only difference between this comparative example and Example 3 is that the matrix is composed of the following components by mass percentage: C 0.06%, Si 0.4%, Mn 1.2%, Cr 0.8%, N 0.02%, P 0.016%, S 0.006%, Ni 0.2%, Cu 0.35%, Ti 0.05%, Nb 0.02%, with the balance being Fe and other unavoidable impurities.
[0034] Comparative Example 4 The only difference between this comparative example and Example 3 is that the matrix is composed of the following components by mass percentage: C 0.06%, Si 0.4%, Mn 1.2%, Cr 0.8%, N 0.02%, P 0.016%, S 0.006%, Ni 0.2%, Cu 0.35%, Ti 0.06%, Nb 0.01%, with the balance being Fe and other unavoidable impurities.
[0035] Experimental Example 1 The high-strength corrosion-resistant steels prepared in Examples 1-3 and Comparative Examples 1-4 were tested for corrosion resistance according to the test methods specified in GB / T 19746-2018 "Corrosion Salt Solution Immersion Test of Metals and Alloys" for 20 days; their low-temperature performance was tested according to the methods specified in GB / T229-2020 "Charpy Pendulum Impact Test Method for Metallic Materials". The test results are shown in Table 1. Table 1. Performance test results of the high-strength corrosion-resistant steels prepared in Examples 1-3 and Comparative Examples 1-4
[0036] Compared with Comparative Examples 1-3, the high-strength corrosion-resistant steel prepared in Examples 1-3 had a higher low-temperature transverse impact energy than that in Comparative Examples 1-4, indicating that adjusting the ratio of Ti and Nb to N in the matrix to Ti / N=3-3.5 and Nb / N=1-1.2 can significantly improve the low-temperature toughness of the steel. Furthermore, the corrosion rate of the high-strength corrosion-resistant steel prepared in Examples 1-3 was significantly lower than that in Comparative Examples 1-4, indicating that adjusting the ratio of Ti and Nb to N in the matrix to Ti / N=3-3.5 and Nb / N=1-1.2 can also improve the corrosion resistance of the steel.
[0037] Experiment Example 2 The high-strength corrosion-resistant steels prepared in Examples 3-7 were tested according to the test methods specified in GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature". The test results are shown in Table 2. Table 2 Performance test results of the high-strength corrosion-resistant steels prepared in Examples 3-7
[0038] Compared with Examples 3 to 7, the tensile strength of the high-strength corrosion-resistant steel prepared in Examples 4 to 7 is higher than that in Example 3, indicating that adding alumina and silicon carbide-coated cerium oxide as reinforcing phases can improve the strength of high-strength corrosion-resistant steel. The tensile strength of the high-strength corrosion-resistant steel prepared in Example 6 is higher than that in Examples 4, 5 and 7, indicating that the mass ratio of cerium oxide, silicon carbide and alumina is 90:7:5, which has the best effect on improving the strength of steel.
[0039] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-strength corrosion-resistant steel, characterized in that, The mixture comprises a matrix and a reinforcing phase. The matrix consists of the following components in mass percentage: C 0.04%~0.08%, Si 0.21%~0.55%, Mn 1.0%~1.5%, Cr 0.5%~1.0%, N 0.015%~0.025%, P ≤0.02%, S ≤0.008%, Ni 0.1%~0.3%, Cu 0.2%~0.5%, Ti 0.045%~0.0875%, Nb 0.015%~0.03%, with the balance being Fe and other unavoidable impurities, wherein Ti / N = 3~3.5 and Nb / N = 1~1.
2. The reinforcing phase comprises alumina and silicon carbide-coated cerium oxide; The method for preparing cerium oxide coated with alumina and silicon carbide includes the following steps: Alumina, silicon carbide and cerium oxide are mixed, ethanol is added, and the mixture is ball-milled, dried, calcined and ground to obtain alumina and silicon carbide coated cerium oxide. The mass ratio of cerium oxide, silicon carbide and aluminum oxide is 90:6~8:4~6; The total mass ratio of cerium oxide, silicon carbide, and aluminum oxide to the volume ratio of ethanol is 10g:30~40mL; The calcination temperature is 850~950℃.
2. A method for preparing a high-strength corrosion-resistant steel, used to prepare the high-strength corrosion-resistant steel according to claim 1, characterized in that, Includes the following steps: Weigh the components according to the weight percentage of the matrix, melt them to obtain molten steel; add the reinforcing phase to the molten steel, mix, and continuously cast to obtain a steel billet; The steel billet is heated, rough rolled, finish rolled, cooled, and coiled to obtain high-strength corrosion-resistant steel.
3. The method for preparing a high-strength corrosion-resistant steel according to claim 2, characterized in that, The casting speed is 2~2.5m / min.
4. The method for preparing a high-strength corrosion-resistant steel according to claim 2, characterized in that, The heating temperature is 1200-1300℃, and the holding time is 60-80 minutes.
5. The method for preparing a high-strength corrosion-resistant steel according to claim 2, characterized in that, The rough rolling process involves descaling before rough rolling. The initial rolling temperature is 1100~1200℃, and the final rolling temperature is 1030~1130℃.
6. The method for preparing a high-strength corrosion-resistant steel according to claim 2, characterized in that, The process involves descaling before finishing rolling, with the initial rolling temperature being 930~1030℃ and the final rolling temperature being 830~900℃.
7. The method for preparing a high-strength corrosion-resistant steel according to claim 2, characterized in that, During the cooling process, the temperature of the laminar water is 25~30℃, and the cooling rate is 20~30℃ / s; The winding temperature is 530~600℃.
Citation Information
Patent Citations
Method for preparing silicon carbide porous ceramics through low temperature sintering assisting
CN105601319A
Low-temperature corrosion-resistant steel for high-cold frozen soil environment and preparation method of low-temperature corrosion-resistant steel
CN121428415A